2007
DOI: 10.1152/ajpheart.00700.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous interleukin-1α promotes a proliferative and proinflammatory phenotype in human vascular smooth muscle cells

Abstract: Schultz K, Murthy V, Tatro JB, Beasley D. Endogenous interleukin-1␣ promotes a proliferative and proinflammatory phenotype in human vascular smooth muscle cells. Am J Physiol Heart Circ Physiol 292: H2927-H2934, 2007. First published February 9, 2007 doi:10.1152/ajpheart.00700.2006.-During vascular disease and following injury, vascular smooth muscle cells (VSMC) proliferate and produce inflammation-promoting cytokines and chemokines. Similar phenotypic changes can be elicited in vitro by activation of Toll-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 37 publications
2
39
1
5
Order By: Relevance
“…21,22 The present study demonstrated that inhibition of s-EH reduced circulating inflammatory mediators, including IL-1␣, IL-6, and murine IL-8-KC, all of which have been reported as being involved in the development of atherosclerosis. [23][24][25][26][27] Furthermore, the present data have demonstrated that s-EH inhibition decreased the expression of proinflammatory genes in arterial wall, such as VCAM-1 and ICAM-1, which are critical adhesion proteins playing an early and essential role in the pathogenesis of atherosclerosis. 28 The pathohistological examination also revealed a marked reduction of inflammatory cell infiltration and extracellular matrix destruction in the vascular wall in AR9276-treated mice, which was also accompanied by a reduction of proinflammatory mediators.…”
supporting
confidence: 61%
“…21,22 The present study demonstrated that inhibition of s-EH reduced circulating inflammatory mediators, including IL-1␣, IL-6, and murine IL-8-KC, all of which have been reported as being involved in the development of atherosclerosis. [23][24][25][26][27] Furthermore, the present data have demonstrated that s-EH inhibition decreased the expression of proinflammatory genes in arterial wall, such as VCAM-1 and ICAM-1, which are critical adhesion proteins playing an early and essential role in the pathogenesis of atherosclerosis. 28 The pathohistological examination also revealed a marked reduction of inflammatory cell infiltration and extracellular matrix destruction in the vascular wall in AR9276-treated mice, which was also accompanied by a reduction of proinflammatory mediators.…”
supporting
confidence: 61%
“…This 158 evidence raises questions about how TLR signaling alters the different compartments of blood vessels and the interaction between the layers of the vascular wall. Previous research has focused on TLR signaling in endothelial cells as well as immune cells that infiltrate the vascular wall (Yang et al, 2005a(Yang et al, ,b, 2006de Graaf et al, 2006;Schultz et al, 2007;Pryshchep et al, 2008;Zimmer et al, 2011;Liang et al, 2013). Currently, there is a growing interest in the adventitial compartment of blood vessels and in particular the adventitial fibroblast, which play an important role in regulating the structure and function of the vascular wall (Stenmark et al, 2013;El Kasmi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TLR4 deficiency improved indices of atherosclerosis in both ApoE- (Michelsen et al, 2004) and LDL receptordeficient mice (Ding et al, 2012). Moreover, TLR4 has an important role in the proatherogenic response of macrophages to oxidized LDL and lipid accumulation (Kazemi et al, 2005;Miller, 2005), proinflammatory and proliferative phenotype in vascular smooth muscle cells (de Graaf et al, 2006;Yang et al, 2005b;Schultz et al, 2007), and endothelial dysfunction (Yang et al, 2005a;Liang et al, 2013). On the other hand, the contribution of TLR5 to atherosclerosis is relatively sparse.…”
Section: A Atherosclerosismentioning
confidence: 99%
“…As a result, this promoted a HASMCs inflammatory phenotype and vascular remodeling [112]. In addition, in 2007, Schultz and colleagues [113], using human VSMCs cell cultures derived from digestion of human coronary artery or pulmonary artery, detected that autocrine actions of endogenous interleukin (IL)-1 α, mediated at least in part via IL-1RI signaling, contributed to a pro-proliferative and proinflammatory phenotypic shift in TLR-4-activated human VSMCs. As a consequence, they suggested a pathogenic role of TLR-4 pathway in vascular disorders.…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%